Relative effectiveness of bivalent COVID-19 vaccine: a systematic review and meta-analysis - Cheng, Meng-qun; Li, Rong; Weng, Zhi-ying; Song, Gao (Frontiers in Medicine, 2024)
Objective The rapid development of COVID-19 bivalent vaccines (BVs) has encompassed both the original virus strains and the variant strain. However, the effectiveness of BVs is largely unknown. Therefore, we conducted a systematic review and meta-analysis of the effectiveness of BVs. Methods Literature research was conducted through PubMed, Cochrane Library, Embase, and Web of Science up until November 4, 2023. Both randomized control trials and observational studies were considered for inclusion. Pooled estimates were calculated using a random effects model. The Newcastle-Ottawa Scale (NOS) was used to assess the risk of bias in cohort and case–control studies. Results A total of 1,174 articles were reviewed and 22 eligible studies were included. All included studies were observational (15 cohort studies, 7 case–control studies). The total number of participants was 39,673,160, and the number of people vaccinated with BVs as an intervention group was 11,585,182. Two mRNA BVs were mainly involved, including the ancestral strain and the BA.1 or BA.4–5 variants. Meta-analysis results showed, compared with the monovalent vaccines (MVs), the relative effectiveness (rVE) of the BVs in COVID-19-associated infections/symptomatic infections, illnesses, hospitalizations, and deaths was 30.90% [95% confidence interval (CI), 8.43–53.37], 39.83% (95% CI, 27.34–52.32), 59.70% (95% CI, 44.08–75.32), and 72.23% (95% CI, 62.08–82.38), respectively. For those aged 50 years and older, BVs provided an additional 49.69% (95% CI, 41.44–57.94) effective protection compared with MVs. During the dominance period of the omicron XBB variant strain, BVs provided an additional 47.63% (95% CI, 27.45–67.82) effective protection compared with MVs. Conclusion Our findings show that the rVE of BVs in preventing COVID-19-associated infections, symptomatic infections, illnesses, hospitalizations, and deaths is higher compared to MVs. Particularly for people over 50 years of age and during the Omicron variant XBB dominance phase, BVs provided superior protection. Therefore, BVs may have a broader application in the prevention and control of coronaviruses variant.